Factors Affecting Mobile Banking Use Behavior: Case Study at Bank BNI Jakarta - Fathihani; Saputri, Ika Puji; Randyantini, Vely (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The aim of this study was to determine the effect of Perceived Ease of Use, Perceived Usefulness, and Effort Expectancy on Intention to Use Mobile Banking. It is hoped that the results of this research will contribute to Bank BNI in using the right strategy so that interest in using Mobile Banking can increase. The population in this study are customers who use the Mobile Banking application of PT Bank Negara Indonesia (BNI) in DKI Jakarta, the sample used is 100 respondents spread across the Jakarta area. Data collection was carried out using a questionnaire method in which respondents answered questions arranged in the form of choices and scaled questions using a Likert scale (1-5). The method used in this study is a quantitative analysis using SEM analysis tools and SmartPLS 3.3 tools. The research results show that Perceived Ease of Use and perceived Usefulness, have an effect on Intention to Use Mobile Banking while Effort Expectancy has no effect on Intention to Use Mobile Banking